1997
DOI: 10.1111/j.1745-4557.1997.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

ALKALI‐PROCESSED SWEETPOTATO FRENCH FRIES1

Abstract: A combination of alkali (sodium phosphate or calcium chloride) infiltration and blanching and their order of application were studied for their efect on the sensory and physico-chemical (moisture, fat, sugars, and shear force) quality of sweetpotato French fries (SPFF) made from sweetpotatoes (SP) stored for 3 months or 1 year. Sensory quality (taste, texture, and overall acceptability) were evaluated using a nine-point hedonic scale. Treatment of SP strips with sodium phosphate solutions prior to blanching ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Some of the value-added products that can be produced from sweetpotato include: puree (Walter, Truong, & Espinel, 1999), French-fry-type product (Sylvia, Walter, & Giesbrecht, 1997), patties (Hoover & Walter, 1983), starch and flour (Dansby & Bovell-Benjamin, 2003;Jangchud, Phimolsiripol, & Haruthaithanasan, 2003;Rahman, Wheatley, & Rakshit, 2003) and dried chips (Akpapunam & Abiante, 1991;Kieras, Mills, Knabel, & Maretzki, 2002). Value-added processing of sweetpotato into dried chips is one of the most promising because of the longer shelf life and superior handling characteristics of the chips in comparison to other products.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the value-added products that can be produced from sweetpotato include: puree (Walter, Truong, & Espinel, 1999), French-fry-type product (Sylvia, Walter, & Giesbrecht, 1997), patties (Hoover & Walter, 1983), starch and flour (Dansby & Bovell-Benjamin, 2003;Jangchud, Phimolsiripol, & Haruthaithanasan, 2003;Rahman, Wheatley, & Rakshit, 2003) and dried chips (Akpapunam & Abiante, 1991;Kieras, Mills, Knabel, & Maretzki, 2002). Value-added processing of sweetpotato into dried chips is one of the most promising because of the longer shelf life and superior handling characteristics of the chips in comparison to other products.…”
Section: Introductionmentioning
confidence: 99%
“…Development of texturized SP puree was reported by Truong & Walter (1994) and Truong et al (1995). Restructured French fries were also developed by Walter et al (2002) and Sylvia et al (1997).…”
Section: Introductionmentioning
confidence: 90%
“…5.8-6.0; (3) same as treatment (2) except the sodium acetate solution contained 2% calcium chloride. VI and blanching were as described earlier (Walter et al 1993;Sylvia et al 1997).…”
Section: Processingmentioning
confidence: 99%
“…Walter et al (1993) showed that infiltratlon of SP tissue with bases, followed by blanching and neutralization, caused a significant increase in firmness retention of sliced SP strips when compared with blanched, untreated strips. Later research (Sylvia and Walter 1997) demonstrated that infiltration of a dilute Na,PO, solution, followed by blanching and neutralization, gave the most acceptable French frytype product from SP stored for up to 1 year before processing. In this report we discuss the use of the alkali infusion-neutralization process to minimize softening and disintegration of SP stored for 1, 5 and 10 months before canning.…”
Section: Introductionmentioning
confidence: 99%